Evaluation of Motor Vehicle Tax Payments through the Electronic One-Stop Administration System (E-Samsat) at the UPT Revenue Management Kubang, Kampar Regency - Syaprianto, Syaprianto; Sirait, Ester Melyana (Universitas Muhammadiyah Tapanuli Selatan, 2022)
In the current era of globalization, the government must quickly improve itself to increase public satisfaction with the services provided. One of the efforts to increase public satisfaction in making motor vehicle tax payments is by implementing the electronic one-stop single administration system abbreviated as (e-samsat). This study aims to evaluate the implementation of motor vehicle tax payments through the electronic one-stop single administration system (e-samsat) at the UPT Revenue Management Kubang, Kampar Regency. The research method used in this research is qualitative, focusing on analyzing empirical conditions. In contrast, the data collection techniques used in this study are interviews and documentation. In this study, researchers used evaluation theory, according to William N. Dunn (2003), with effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy indicators. This research concludes that implementing online payments or e-samsara is still not optimal because many taxpayers still need to learn about online payments or use e-samsara. The inhibiting factors are the minimal knowledge of employees about e-samsat, the need for socialization, and inadequate facilities and infrastructure.